Analisis Kebijakan Pemerintah dalam Pengelolaan Badan Usaha Milik Desa di Desa Pocong Kecamatan Lamba Leda Selatan Kabupaten Manggarai Timur - Fridolan Adi Putra; Nasir Nasir; Abdul Halim (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The village government policy in managing BUMDes has not been running properly and there has not been much role of the village government in managing BUMDes Mentari Pagi. Therefore, the village government policy in managing BUMDes must be implemented properly and the village government must be directly involved or increase its role in fostering the management of BUMDes Mentari Pagi in Pocong Village, Lamba Leda Selatan District, East Manggarai Regency. This study aims to determine the village government policy in managing BUMDes in Pocong Village, Lamba Leda Selatan District, East Manggarai Regency and to determine the role of the village government in managing BUMDes in Pocong Village, Lamba Leda Selatan District, East Manggarai Regency. This study uses a field research method with a qualitative descriptive analysis approach. The results of this study indicate that there is still a lack of community involvement in the management of BUMDes in Pocong Village. This is because the community is busy with their work individually and the village government is less open to BUMDes administrators in managing BUMDes and the role of the Pocong Village Government in managing BUMDes in this case the Pocong village government has not carried out its duties and authorities to the maximum extent possible. It can be seen from the answers from 7 people who were used as respondents, 100% answered poorly, thus the management of Pocong Village's business entity lacks transparency.